2010
DOI: 10.5453/jhps.45.161
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Global 222Rn Flux Density from the Earth's Surface

Abstract: Global 222 in the period of 1979-2007 using an 222 Rn exhalation model based on a porous media diffusion theory. This exhalation model calculated the 222 226 Ra content, soil water saturation, and soil temperature. The -2 s -1 . The annual variation in the -2 s -1 in March to a maximum of 23.6 mBq m -2 s -1 in September. The regional averages for the annual flux density varied from 8.3 mBq m -2 s -1 for the northern part of North America to 33.5 mBq m -2 s -1 for Australia. The latitudinal distribution of zona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…for each wind sector or soil moisture content (if monitored), or use a process model (e.g. Hirao et al, 2010;Karstens et al, 2015a) for extrapolating the flux after calibration with SPOT-EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…for each wind sector or soil moisture content (if monitored), or use a process model (e.g. Hirao et al, 2010;Karstens et al, 2015a) for extrapolating the flux after calibration with SPOT-EC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several approaches have been applied to quantify 222 Rn surface fluxes: (1) using gamma dose radiation as a proxy for 222 Rn (Szegvary et al, 2007;Manohar et al, 2016) and (2) modelling the production and transport of 222 Rn in soils (Hirao et al, 2010;Karstens et al, 2015a). These efforts have provided new tools for studying the driving mechanisms behind the 222 Rn soil flux on relatively large spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…These values are considered much higher than typical 222 Rn emission known for Europe, where Szegvary et al (2009) suggested half of the continent has emissions ranging from 8.33 to 14.6 mBq m -2 s -1 (0.40 to 0.70 atom m -2 20 s -1 ). Hirao et al (2010) also found that, to better match surface observations at Hachijo Island, a volcanic island about 287 kilometers south of Tokyo in the Philippine Sea, the emissions over East Asia would need to be increased by a factor of 1.69.…”
Section: Excessive 222 Rn Emissions In East Asiamentioning
confidence: 97%
“…Consistently, Zahorowski et al (2005) found Based on three-year winter-time 222 Rn observations at Sado Island, Japan, and associated trajectory analyses, Williams et al (2009) suggested that emission fluxes can be 1.75 times higher in the lower 15 latitude bands over the Asian continent compared to higher latitudes. In an inverse modeling of Asian 222 Rn emissions, Hirao et al (2010) showed an area-weighted average 222 Rn emission of 33.0 mBq m -2 s -1 (~1.57 atom m -2 s -1 ) in Asia with the highest emissions found in central and southeastern Asia. These values are considered much higher than typical 222 Rn emission known for Europe, where Szegvary et al (2009) suggested half of the continent has emissions ranging from 8.33 to 14.6 mBq m -2 s -1 (0.40 to 0.70 atom m -2 20 s -1 ).…”
Section: Excessive 222 Rn Emissions In East Asiamentioning
confidence: 99%
See 1 more Smart Citation